2021
DOI: 10.3390/w13101420
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Titanium Dioxide with Formaldehyde in the Presence of Quartz Sand under Static and Dynamic Conditions

Abstract: Formaldehyde (FA) is an extremely active compound that is widely used in numerous applications. Given that FA is a known carcinogen, it is essential to remove it from the environment. Titanium dioxide (TiO2), due to its special physicochemical properties, is a promising adsorbent for the removal of specific organic compounds from aqueous solutions. In this study, the interaction of TiO2 with FA in the presence and absence of quartz sand, the most common mineral on the Earth’s surface, was investigated under st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the presence of NaCl does not affect FA retention by the quartz sand (Fountouli et al., 2019), and that FA can sorb significantly onto TiO 2 nanoparticles (Stefanarou & Chrysikopoulos, 2021). Furthermore, no significant FA retention by the quartz sand has been observed in batch experiments or in flowthrough experiments in packed columns under both water saturated and unsaturated conditions (Fountouli et al., 2019; Fountouli & Chrysikopoulos, 2020).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that the presence of NaCl does not affect FA retention by the quartz sand (Fountouli et al., 2019), and that FA can sorb significantly onto TiO 2 nanoparticles (Stefanarou & Chrysikopoulos, 2021). Furthermore, no significant FA retention by the quartz sand has been observed in batch experiments or in flowthrough experiments in packed columns under both water saturated and unsaturated conditions (Fountouli et al., 2019; Fountouli & Chrysikopoulos, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies revealed that FA adsorbs onto TiO 2 surfaces mainly in a monodentate configuration (Setvin et al., 2017), and FA adsorption onto TiO 2 nanoparticles occurs mainly due to a chemisorption process with pseudo‐second‐order kinetics (Stefanarou & Chrysikopoulos, 2021). Also, TiO 2 nanoparticles may facilitate the transport of coexisting pollutants and colloidal and biocolloidal particles through porous media (Cai et al., 2013, 2014, 2019; G. Chen et al., 2012; Chowdhury et al., 2012; Fang et al., 2016; Guo et al., 2018; Syngouna et al., 2017; Xia et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The fitting Q e 2 values of 3.227 and 14.404 mg·g −1 obtained from the two fiber membrane differed very little from the actual tested Q e values of 3.16 and 13.69 mg·g −1 , respectively. Therefore, the adsorption process of TP0 and TP4 fiber membranes conforms to the pseudo‐second‐order kinetic model, which is an adsorption process based on chemical adsorption, 69 indicating that a large amount of MB is adsorbed through the covalent bond between the fiber membrane and MB. The adsorption capacity of TP4 fiber membrane was significantly higher than that of TP0 fiber membrane and other PLA composite fiber membranes 70 .…”
Section: Resultsmentioning
confidence: 60%
“…The fate of ECs and their transport into groundwater systems are critical in understanding groundwater pollution. Many researchers studied the fate of many ECs and their transport into soil and groundwater systems, namely formaldehyde [32,33], titanium dioxide [34], cotransport of biocolloids [35], cotransport of human adenoviruses [36], cotransport of clay colloids [37,38], transport of bio colloids [39], and cotransport of Pseudomonas putida and kaolinite particles [40].…”
Section: Introductionmentioning
confidence: 99%